Competence in oral communication and public speaking - Nuval, Evarista G. (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2014)
This book used excerpts from various works of literary luminaries to illustrate clearly the different vowel sounds and consonant sounds of American English.
Preface -- Acknowledgement -- PART ONE. Basic skills in oral communication -- Chapter 1. Breathing and breath control -- Chapter 2. Voice and projections -- Chapter 3. Oral communication -- Chapter 4. The sounds of American English -- Chapter 5. The phonetic symbols -- Chapter 6. Stress and rhythm -- Chapter 7. Phrasing and blending -- Chapter 8. Intonation -- PART TWO. Essentials of public speaking -- Chapter 9. Role of communication in society -- Chapter 10. Communication contexts -- Chapter 11. Verbal and nonverbal symbols -- Chapter 12. Delivery -- Chapter 13. Communication apprehension -- Chapter 14. Speech -- Chapter 15. Listening -- Chapter 16. The writing process -- Chapter 17. Speeches for delivery -- Diagnostic Test -- Glossary -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: ORAL COOMUNICATION -- SPEECH -- PUBLIC SPEAKING